Bill & Ted's bogus journey [videorecording (DVD)] - Matheson, Chris; Solomon, Ed; Newman, David, 1954- (MGM Home Entertainment, 2001)
When the evil De Nomolos dispatches robots to kill Bill & Ted, not only is the future of the universe at stake, but there's no way they can win the battle of the bands. Luckily, when they knock on Death's door, he answers, becoming their faithful servant in a whacked-out journey through Heaven, Hell and San Dimas, California. Bill & Ted meet Martians, marry their historical girlfriends, & even learn how to play the guitar.